2017
DOI: 10.1007/s00436-017-5597-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and economic analysis of two treatment regimens using toltrazuril in lambs naturally infected with Eimeria spp. on pasture

Abstract: This study evaluated the efficacy and the economic viability of two anticoccidial treatment regimens tested in lambs naturally exposed to Eimeria spp. re-infections in a grazing system during a 140-day period. Twenty-four suckling lambs were distributed into three groups based on the individual count of oocysts per gram of feces (OPG) and body weight. Animals were treated with toltrazuril 5% (20 mg/kg) at 14- (GI) or 21-day (GII) intervals, and GIII was kept as untreated control. A cost-benefit analysis of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…The classification thresholds used in our study were based on the figures of 90% and 95% used by Geurden et al (2015) and Peña-Espinoza et al (2016) in anthelmintic studies, as there is currently no published target efficacy available for toltrazuril. The same classification targets were used by de Souza Rodrigues et al (2017) who investigated the efficacy of different toltrazuril treatment strategies in Brazil. However, we note that although these figures seem reasonable in the absence of alternatives, there is no specific evidence to support the direct translation of 90% and 95% efficacy targets from their intended context of estimating the arithmetic mean efficacy of anthelmintic compounds against nematodes to the quite different context of estimating the geometric mean efficacy of anticoccidial compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The classification thresholds used in our study were based on the figures of 90% and 95% used by Geurden et al (2015) and Peña-Espinoza et al (2016) in anthelmintic studies, as there is currently no published target efficacy available for toltrazuril. The same classification targets were used by de Souza Rodrigues et al (2017) who investigated the efficacy of different toltrazuril treatment strategies in Brazil. However, we note that although these figures seem reasonable in the absence of alternatives, there is no specific evidence to support the direct translation of 90% and 95% efficacy targets from their intended context of estimating the arithmetic mean efficacy of anthelmintic compounds against nematodes to the quite different context of estimating the geometric mean efficacy of anticoccidial compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Although the initial efficacy values have not been provided for toltrazuril by the manufacturer, several studies have investigated its effect on oocyst excretion. For example, its efficacy has been found to be 96.9-99.9% in the period from 7 to 98 days after first treatment, in a study in which the lambs were treated every 14 days [52]. Other studies have shown toltrazuril efficacies [either provided in the publication or calculated as 1-(mean OPG treated group)/(mean OPG control group) from data in the publication] ranging from 90.0 to 100.0% in the period from two to three weeks after treatment [13,18,19,[53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…This silent illness is hard to detect and expensive to treat. Rodrigues et al (2017) showed that subclinical coccidiosis treatment is economically unfeasible; however, it may be viable when used to prevent weight loss from clinical coccidiosis.…”
Section: Grazingmentioning
confidence: 99%
“…Coccidiosis has considerable economic importance, causing decreases in productivity, low growth performance, diarrhea, and mortality (Khodakaram-Tafti & Hashemnia, 2017). Furthermore, treatment costs are high and are not always economically viable, especially in subclinical infections (Rodrigues et al, 2017). Many Eimeria infections in sheep are asymptomatic; however, more frequently in lambs, some species have been associated with diarrhea and stunted growth (Chartier & Paraud, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation